2004
DOI: 10.1158/0008-5472.can-04-2402
|View full text |Cite
|
Sign up to set email alerts
|

Folate Is Associated with the Natural History of High-Risk Human Papillomaviruses

Abstract: Several micronutrients have been implicated in cervical carcinogenesis. However, their mode of action is still a matter of speculation. In particular, it is unclear whether certain nutrients reduce the probability of acquiring high-risk human papillomavirus (HPV) or whether they facilitate the clearance of high-risk HPV. We conducted a 24-month prospective follow-up study to test the hypothesis that systemic concentrations of folate are associated with the occurrence and duration of high-risk HPV infections af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 30 publications
2
59
0
6
Order By: Relevance
“…Therefore pregnancy appears to be a potential risk factor for enhanced viral replication/ expression and along with this extremely low immunity in Indian/Asian pregnant women, a vast majority of whom suffer from malnutrition and folate deficiency (43), which also contribute to liver injury, low immunity, and disease severity, leading to death (see Figure 8). Highly reduced immunocompetence is known to be associated with folate deficiency (43)(44)(45), which increases the multiple viral infection and/or increased viral load (43), including multifactorial disorders, in the Asian population (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore pregnancy appears to be a potential risk factor for enhanced viral replication/ expression and along with this extremely low immunity in Indian/Asian pregnant women, a vast majority of whom suffer from malnutrition and folate deficiency (43), which also contribute to liver injury, low immunity, and disease severity, leading to death (see Figure 8). Highly reduced immunocompetence is known to be associated with folate deficiency (43)(44)(45), which increases the multiple viral infection and/or increased viral load (43), including multifactorial disorders, in the Asian population (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore pregnancy appears to be a potential risk factor for enhanced viral replication/ expression and along with this extremely low immunity in Indian/Asian pregnant women, a vast majority of whom suffer from malnutrition and folate deficiency (43), which also contribute to liver injury, low immunity, and disease severity, leading to death (see Figure 8). Highly reduced immunocompetence is known to be associated with folate deficiency (43)(44)(45), which increases the multiple viral infection and/or increased viral load (43), including multifactorial disorders, in the Asian population (46,47). A selective high susceptibility of Asian pregnant women to viral hepatitis leading to liver failure could also be due to ethnicity-associated host genetic susceptibility, particularly associated with the genes of the major histocompatibility complex (MHC), which has a strong effect on immune response to viral antigens (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of sample collection and methodologies used to assess MTHFR polymorphism and folate, vitamins B-12, A, E, C and total carotene are published elsewhere (10,15). RBC samples frozen at −80°C within two hours of collection were used to determine riboflavin status using the erythrocyte glutathione reductase activity coefficient (EGRAC), a preferred method for evaluating riboflavin status (16).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Nutritional status and food consumption may be important HPV cofactors that increase risk of persistence and progression to cervical intraepithelial neoplasia (CIN; Garcia-Closas et al, 2005). Previous research has shown that high folate status significantly influences the natural history of infections with high-risk HPV (Piyathilake et al, 2004) and lower likelihood of developing high-risk HPV-associated CIN grades higher than 2 (CIN 2 þ ; Piyathilake et al, 2007Piyathilake et al, , 2009). The apparent role of folate in cervical carcinogenesis has lead to the interest in folate metabolism enzymes that may be the cofactors linking folate deficiency and cervical carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%